ANALISIS STRATEGI DISTRO SYAICHONA BANGKALAN DALAM MENGATASI VOLUME PENJUALAN - ily, luluk illiyah (Universitas Muhammadiyah Surabaya, 2023)
The growht of the business world is currently increasing marked by increasingly fierce competition. Fashion distribution is a clothing produvt that is produced by a particular clothing store and has characteristics that distinguish it from other types of clothing products from a fashion store. Distro clothing products that have designs that prioritize the distinctive appearance of urban youth by raising concepts such as music or sports and etc. However, it is didderent from tha Syaichona distro which carries the theme of Islamic clothing, because it is in a Islamic boarding school. This has resulted in the difficulty for Syaichonaâ€™s distro to develop its business, in the end the business it runs is unable to compete with other distro out there. The purpose of this study was to analyze the strategy used by the syaichona distro in dealing with sales volume. In this study using qualitative research using the case study method, the use of qualitative approach in this study is to match the research reality. The data sources obtained include primary data sources in this study using persons/ namely obtained through interviews with respondents, namely the head of Syaichona sistro, syaichona distro employess, and consymers. As well as secondary data such as other related reseatch. In dealing with tis problem, Syaichona;s distro carries out a strategy starting form being skilled in creating interesting ideas, further increasing its performance towards accuracy in selecting higher quality products, the level of the latest fashion tren, and taking steps to do good marketing such as utilizing the media social services such as innstagram, facebook, an d shoperr to market and update more to provide effective information to customers when new items arrive, and always have a discount.Â Keyword: strategy, distro syaichona, sales volume